การเปรียบเทียบทักษะทางวิชาชีพของผู้สอบบัญชีรับอนุญาตและนักบัญชีในจังหวัดเชียงใหม่ - ณัฐพล มอญเพชร์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this independent study is to compare the Professional Skills of Accountants and Certified Public Accountants in Chiang Mai Province. The sample group is consisted of 200; as 100 person who are accountants and 100 person who are Certified Public Accountants. The data obtained from questionnaires were analyzed by Descriptive Statistics including frequency, percentage and means, as well as Inferential Statistics as t-test and anova. It was shown that the samples were consisted of female, aged 31 – 40 years old, who have bachelor degree, work as an accountant and working experience is more than 15 years. Almost of the samples work in private companies that employ 1 – 5 accountants. They improve their Professional Skills by using the internet. Those samples who are accountants have the average score of Professional Skills at “good” level (3.74). The highest average score is Intellectual Skills, the second is Personal Skills. But Organizational and Business Management Skills is the lowest score. As for those who are Certified Public Accountants have the average score of Professional Skills at “good” level (4.19). The highest average score is Intellectual Skills, the second is Interpersonal and Communication Skills. But Personal Skills is the lowest score. In addition, the study found the significant difference of between accountants and certified public accountants in a statistical significance of 0.05 (p = 0.05) in 4 skills (Intellectual Skills, Technical and Functional Skills, Personal Skills and Organizational and Business Management Skills), but Interpersonal and Communication Skills was not significantly different at a statistical significance of 0.05.